Studies in P.Beatty III (P47): The Codex, Its Scribe, and Its Text - Malik, Peter (Tyndale bulletin, 2017)
The importance of papyri in NT textual criticism, if properly understood, is difficult to overestimate. Despite their state of preservation, they allowed the critics to move beyond the fourth-century "barrier" of the Constantinian period, in which the earliest "Great majuscules" were produced. The early papyri thus provided a venue for revisiting previous theories concerning transmission history and even some of the "canons" of textual criticism. And perhaps of equal significance is the fact that the early papyri have provided the historians with valuable evidence of early Christian material culture and worship. Although to varying degrees this applies to all the papyri from the pre-Constantinian time, it is particularly true of those from Chester Beatty (P45-47) and Bodmer (P66, 72, 75) collections.